In vitro inhibition kinetics of crocodylus mindorensis (Philippine crocodile) serum against human immunodeficiency virus type I reverse transcriptase - Hinay, Alfredo A.
The study aimed to determine the inhibition kinetics of Crocodylus mindorensis (Philippine crocodile) serum against recombinant HIV-1 Reverse Transcriptase (RT) using Enzyme-linked Immunosorbent Assay. The study utilized and experimental design where different concentrations of Philippine crocodile serum were used to determine its quantitative inhibitory effect and mechanism of inhibition against HIV-1 reverse transcriptase activity. A colorimetric enzyme immunoassay that incorporates digoxigenin and biotin-labeled dUTP into DNA were used for the assay (Roche Version 13.0,2010). In addition, the kinetic activity of HIV-1 Reverse transcriptase was studied to determine the mechanism of enzyme inhibition by Philippine crocodile serum. The source of the crocodile serum was the Davao Crocodile Park located in Gadi Road, Talomo, Davao City.